Analisis User Experience Game Edukasi menggunakan User Experience Questionnaire - Annafi, Farrel Rakha (LPPM & Fakultas Teknologi Informasi UNSAP, 2024)
Digital Games have become ingrained in our daily routine in this day and age. Digital Games can be used as teaching aids due to the increasing support of computer and mobile technology. In terms of education, Digital Games not only provide interesting and entertaining activities, but also activities that help students acquire specific topics. Digital Games can be used to teach English using RPG types as in this study. The purpose of this study is to evaluate the quality of user experience of the English educational Digital Game. The evaluation method used in this research is the User Experience Questionnaire (UEQ) method. The UEQ method is a simple way to find out how well interactive products work for users. By using as many as 22 respondents filled out the questionnaire used to collect data in this study. Based on the analysis that has been done, the results show that the evaluation of the six aspects is positive. Therefore, English educational games can be used as learning media well.